2021
DOI: 10.3390/antiox10081248
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Mitigates Osteoblast Senescence and Counteracts Bone Loss through Oxidation Resistance-1 Control of FoxO3 Methylation

Abstract: Senescent osteoblast overburden accelerates bone mass loss. Little is understood about microRNA control of oxidative stress and osteoblast senescence in osteoporosis. We revealed an association between microRNA-29a (miR-29a) loss, oxidative stress marker 8-hydroxydeoxyguanosine (8-OHdG), DNA hypermethylation marker 5-methylcystosine (5mC), and osteoblast senescence in human osteoporosis. miR-29a knockout mice showed low bone mass, sparse trabecular microstructure, and osteoblast senescence. miR-29a deletion ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Mechanisms underlying senescent induced changes in MSCs have since then been addressed in multiple studies, identifying important mediators of MSC senescence [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. For instance, several miRNAs have been identified that are involved in regulating senescence and the balance between osteoblastic and adipocytic differentiation of BMSCs [ 52 , 55 , 60 , 61 ]. Lian et al investigated an involvement of miR-29a in age-related bone loss [ 61 ].…”
Section: Cellular Senescencementioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms underlying senescent induced changes in MSCs have since then been addressed in multiple studies, identifying important mediators of MSC senescence [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. For instance, several miRNAs have been identified that are involved in regulating senescence and the balance between osteoblastic and adipocytic differentiation of BMSCs [ 52 , 55 , 60 , 61 ]. Lian et al investigated an involvement of miR-29a in age-related bone loss [ 61 ].…”
Section: Cellular Senescencementioning
confidence: 99%
“…For instance, several miRNAs have been identified that are involved in regulating senescence and the balance between osteoblastic and adipocytic differentiation of BMSCs [ 52 , 55 , 60 , 61 ]. Lian et al investigated an involvement of miR-29a in age-related bone loss [ 61 ]. Knockout and overexpression of miR-29a was associated with exacerbated and reduced bone loss, respectively, in old mice.…”
Section: Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Serum or exosomal miR-29a involves the development of obesity or HFD-induced diabetes [53,54]. Other groups and we have revealed that low serum miR-29-3p or miR-29a levels are present in aged patients with osteoporosis [55] or postmenopausal women with osteoporotic spine fracture [56]. The limitations of this study, we should acknowledge, are that we do not exclude miR-29a signaling in osteoblasts that may directly or indirectly influence adipose tissue metabolism.…”
Section: Discussionmentioning
confidence: 80%
“…In an animal model of obesity, the levels of miR-211, miR-130b, miR-188, and miR-128 were increased [45][46][47][48] (Table 1, Ref. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]). Several microRNAs are known to induce BMSC adipogenesis by inhibiting the activity of the transcription factor RUNX2, which is involved in osteoblastogenesis.…”
Section: Micrornas That Regulate Adipogenesis In Bone Marrowmentioning
confidence: 99%